Analysis of Risk Management and Joint Office Based Business Development in the Real Estate Company Wework - Syaipudin, Latif; Nabila Rizki Amalia (ORGANIZE: Journal of Economics, Management and Finance, 2023)
The purpose of this research is to analyze the management concept of WeWork as a provider of shared office services, so that this business can continue to develop according to the goals set by the organization, especially to make a profit. This research method uses literature study, the approach used is descriptive. In accordance with the study method, various data found from books, articles or data from the internet are then narrated descriptively. The results of this research show that WeWork as a company, after developing and reaching its peak, did not pay attention to the potential losses that occurred. Specifically in this study, the valuation that occurred was at least influenced by the cost of capital and risk management which had an impact on the valuation value that occurred with WeWork in the 2019 era. WeWork's weakness at that time was the difficulty in maintaining its capital injection, because owner Adan Neumann made unproductive spending. This then explains that risk management is also an important thing related to the collapse of WeWork in mid-2019 because at that time there was no thought about the risks that would occur if the company's capital injection ran out.